2010
DOI: 10.7863/jum.2010.29.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Substantia Nigra Features Detected by Sonography and Parkinson Disease Symptoms

Abstract: Objective. The aim of this study was to assess the correlation between substantia nigra (SN) echogenic features and area and the clinical symptoms in patients with Parkinson disease (PD). Methods. Clinical examinations and transcranial sonographic evaluations of the SN were performed in 115 consecutive patients with PD. The presence of tremors, rigidity, bradykinesia, gait disorders, speech disorders, and hypomimia was evaluated according to the motor portion of the Unified Parkinson Disease Rating Scale. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 22 publications
(33 reference statements)
4
11
2
Order By: Relevance
“…This feature is in parallel with the results, where the SN+ correlated with the bilateral bradykinesia and rigidity [35]. The SN+ on the right side was larger to the contralateral clinical symptoms on disease presentation ( p = 0.021), but was not replicated on the left side to the contralateral clinical symptoms ( p = 0.055).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This feature is in parallel with the results, where the SN+ correlated with the bilateral bradykinesia and rigidity [35]. The SN+ on the right side was larger to the contralateral clinical symptoms on disease presentation ( p = 0.021), but was not replicated on the left side to the contralateral clinical symptoms ( p = 0.055).…”
Section: Discussionsupporting
confidence: 86%
“…Grade I of the SN echogenicity was defined as the same echogenicity as the brainstem, grade II - when clearly detectable from the brainstem, grade III- lower signal intensity when comparing to perimesencephalic cisterns, grade IV - the same to perimesencephalic cisterns, grade V - higher than perimesencephalic cisterns [35]. …”
Section: Methodsmentioning
confidence: 99%
“…Although we 16 and others [17][18][19] have shown that echogenic SN area is sensitive to ongoing degeneration of dopaminergic neurons in manifest PD, other reports did not find enlargement of echogenic SN area to be related to the stage of PD. 20,21 Increased prevalence of SN1 in cohorts with malignant melanoma, 15,22 prodromal PD symptoms (eg, hyposmia, 23 rapid eye movement sleep behavior disorder, 24 depression 25 ) or asymptomatic parkin and LRRK2 mutation carriers 26,27 appear to indicate that SN1 at least in some circumstances represents a risk marker of PD rather Correlation between mean echogenic SN size and phenotypical traits as well as odds ratio for detection of echogenic enlarged SN area when presenting with specific characteristics.…”
Section: Discussioncontrasting
confidence: 69%
“…It is not known, however, whether this increased amount of iron in this region is a primary cause of PD, which would cause oxidative stress and injury of dopaminergic neurons, or is a secondary phenomenon in the development of disease. In general, the SN hyperechogenicity is present bilaterally in PD, is more extensive (in terms of echogenic area) on the side contralateral to the more symptomatic side, is stable during the course of the disease, and is clinically associated with rigidity and bradykinesia (19,20) . Despite the controversies, some studies suggest that the larger the echogenic area of the SN, the earlier the onset of PD and the slower the progression of the disease (21,22) .…”
Section: Clinical Significance Of the Hyperechogenicity Of The Substamentioning
confidence: 99%